How do you express 68,070,000,000,000 in Scientific Notation?

Answers

Answer 1
Answer: so since scientific notation is
(a number more than 1 and less than 10) times 10^x

move the decimal place to the left and count the places until the decimal is between the 6 and the 8
the number is 13
6.807 times 10^13 or
6.807e+13
Answer 2
Answer: 6,807 times 10 to the power of 10

Related Questions

Prime factor of 293 in expanded form
What is the quartic root of 64? And how did you figure it out? I'm really confuse on quartic roots.
Number less than 700,000 that rounds to 700,000
Defined the end behavior of the following function f(x)=-x^5+x^2-x
Clare estimates that her brother is 4 feet tall. When they get measured at the doctor’s office, her brother’s actual height is 4 feet, 2 inches. Should Clare's or the doctor's measurement be considered the actual height? Explain your reasoning. What was the error, expressed in inches? What was the error, expressed as a percentage of the actual height?

Simplify negative three fifths times m times quantity negative two sevenths times m minus one fourth end quantity.6 over 35 times m squared plus 3 over 20 times m
negative 6 over 35 times m squared minus 3 over 20 times m
6 over 35 times m squared plus one fourth
negative 6 over 35 times m squared plus 3 over 20 times m

Answers

Answer: ITS C 6/35 M^2 + 1/4

Step-by-step explanation: SO THIS IS THE ANSWER

Answer:

C. 6 over 35 times m squared plus one fourth

Step-by-step explanation:

Moving Company A charges a flat fee of $1200 plus $18 and hour. Company B charges $900 plus $23 an hour. After how many hours would the price be the same regard-less of which company was chosen?

Answers

We need to create two expressions, then equate them in order to find the numbers of hours.


Let X = Number of hours

Let 1200+18x = Company A (Flat Fee + Hourly Rate*Hours)

Let 900+23x = Company B


1200+18x=900+23x\n300+18x=23x\n300=5x\n60=x


After 60 hours, the prices will be the same

Match each expression to the correct verbal description.

Answers

Answer with explanation:

1)

          7x^3+8

we first cube a number x i.e. x^3

and then multiply it by 7 and then finally add 8 to the resulting expression.

2)

       (7x+8)^3

We first multiply the number x by 7 and then add 8 to it and then cube the resulting expression.

3)

                (7x)^3+8

We first multiply x by 7 to get 7x and then cube the number and finally add 8 to it.

4)

               7(x+8)^3

We add 8 to  a number x to get x+8 and then cube it and finally multiply 7 to the resulting expression.

       

(7x)3+8 8 added to the cube of 7x

(7x+8)3 The cube of the sum of 7x and 8

7(x+8)3 7 times the cube of the sum of x and 8

7x3+8 8 added to 7 and x cubed

Write a quadratic equation whose roots are 1+8i and 1-8i

Answers

If 1+8i and 1-8i are the equation's roots, then the quadratic equation is

x² - 2x + 65 = 0.

What is meant by Quadratic equation?

A quadratic equation is written in standard form as y = ax² + bx + c, where a, b, and c are simple numbers. A quadratic equation's factored form is denoted by the expression y = (ax + c) (bx + d), where a, b, c, and d are simple numbers.

Any quadratic problem can be solved using the quadratic formula. The equation is first changed to have the form ax² + bx + c = 0, where a, b, and c are coefficients. After that, we enter these coefficients into the following formula: (-b ± √(b² - 4ac)) / (2a).

If 1+8i and 1-8i are the equation's roots, then:

x - (1 + 8i) = 0 and x - (1 - 8i) = 0 then we get

x - 1 - 8i = 0 and x - 1 + 8i = 0

⇒ (x - 1 - 8i)(x - 1  + 8i) = 0

⇒ x² - x + 8ix - x + 1 - 8i - 8ix + 8i + 64 = 0

⇒ x² - 2x + 65 = 0

The quadratic equation is x² - 2x + 65 = 0.

To learn more about quadratic equation refer to:

brainly.com/question/1214333

#SPJ2

Answer:

x^2-2x+65=0

Step-by-step explanation:

If the roots of this equation are 1+8i and 1-8i, then:

x-(1+8i)=0\nx-(1-8i)=0

And hence:

x-1-8i=0\nx-1+8i=0\n(x-1-8i)(x-1+8i)=0\nx^2-x+8ix-x+1-8i-8ix+8i+64=0\nx^2-2x+65=0

Hope this helps!

What is the answer and work to the equation x+5x-6<12

Answers

x+5=6x and 12+6=18 and 6÷6=x and 12÷6=2 so it is x<2

Estimate the quotient 122.56 divided by 2.98

Answers

122.56\approx123\n\n2.98\approx3\n\ntherefore\n122.56:2.98\approx123:3=(120+3):3=120:3+3:3=40+1=\boxed{41}
122.56÷2.98=4.21765101
41